KEMAMPUAN BERBICARA MELALUI VIDEO AUDIO VISUAL PADA PESERTA DIDIK KELOMPOK B2 TK KEMALA BHAYANGKARI PALU - Femmy Jacoba; Yunidar Nur; Sitti Harisah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
The formulation of the problem of this research, namely how the forms and constraints of the ability to learn speaking through audio-visual videos in group B2 TK Kemala Bhayangkari Palu students and the purpose of this study, are to describe the forms and constraints of learning ability to speak through audio-visual videos in group B2 TK Kemala students. Bhayangkari Palu. The method used is a qualitative research method. The object of this research is the students of group B2 Kindergarten Kemala Bhayangkari Palu. Data collection techniques by observation, interviews, and documentation. Based on the analysis that has been carried out, it can be concluded that the form of learning to speak through audio-visual videos for group B2 Tk Kemala Bhayangkari Palu students is carried out through the following stages: providing learning materials, preparing various alternative media: Whatsapp Group, Youtube, and Zoom, monitoring, and uploading materials. learning in the form of tutorials, videos, student worksheets to media that have been determined or mutually agreed upon. The obstacles found by the teacher in learning speaking based on audio-visual videos for group B2 students were: (1) lack of parental assistance, (2) internet signal/connection, (3) teachers could not interact directly. With regard to the results of the study, the authors suggest that teachers can improve their competence in making innovations that can support the improvement of students' speaking skills by developing good plans for the learning process.